Political Communications Of The Indonesian Democracy Party Struggling (Pdip) In Getting The Most Vote In Deli Serdang In The 2019 Election - Alvin Aulia Rahman Ks; Indira Fatra Deni Peranginangin (LEGAL BRIEF, 2022)
Using qualitative research methods, this study aims to discover how the PDIP party in Deli Serdang conducts political communication and communication/campaign strategies, the factors that influence the success and failure of Legislative candidates, and the candidates' attitudes toward the results of the 2019 presidential election. This study's subjects included several party cadres who ran campaigns as well as the general public. Interviews were used to collect data, which was then analyzed using data triangulation techniques. The findings revealed that the campaign strategies used by party cadres to win their successful and unsuccessful parties were generally the same, namely: campaigner determination, use of campaign media, preparation of distinct messages, and the same target audience.